Provenance of Ross Sea Drift in McMurdo Sound (Antarctica) and implications for middle-Quaternary to LGM glacial transport: New evidence from petrographic data - Perotti, Matteo; Zurli, Luca; Sandroni, Sonia; Cornamusini, Gianluca; Talarico, Franco Maria (Sedimentary Geology, 2018)
The provenance of Ross Sea Drift deposits from the McMurdo Sound region (Antarctica), ranging from middle Quaternary to a Last Glacial Maximum (LGM) age, has been investigated by means of petrographic techniques. A total of 19 bulk till samples from four areas was analyzed for three different granulometric fractions: pebble to cobble, granule, and coarse to very coarse sand grain size. Deposits were classified following the lithological composition of clasts and occurrence of different petrographic groups was evaluated for each sample. Clasts composition predominantly reflects source rocks cropping out in the region between Mackay and Koettlitz glaciers, with McMurdo Volcanic Group rocks being the most represented lithologies in the Royal Society Range foothills, while Granite Harbour Intrusive Complex rocks are more widespread in Taylor and Wright valleys. The lithological distribution of collected samples supports a distal provenance related to a grounded Ross Ice Sheet in Taylor Valley, while the specific distribution of volcanic lithologies in Royal Society Range foothills is evidence for a northward ice flow from Koettlitz Glacier catchment, thus supporting previous glaciological models of an expanded lobe during the LGM. In addition, middle-Quaternary Trilogy Drift composition from Wright Valley accounts for a local provenance, thus allowing the hypothesis of a thickened Wilson Piedmont Glacier rather than a grounded Ross Ice Sheet during past ice advances. (C) 2018 Elsevier B.V. All rights reserved.